1995
DOI: 10.1093/ajcp/103.1.98
|View full text |Cite
|
Sign up to set email alerts
|

Performance of the Coumatrak System in a Large Anticoagulation Clinic

Abstract: There is a need to monitor anticoagulation accurately, inexpensively, and rapidly. The accuracy and precision of a simple fingerstick method was studied in a large outpatient anticoagulation clinic using the Coumatrak method. The Coumatrak apparatus has been studied in the home setting, and three recent reports suggest that it is practical, accurate, and possibly superior to the standard method. These results differ from recently published studies. This technique was found to be less than acceptable in precisi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…14 25 Another study found only 40% of paired samples within 0.5 INR units of each other. 26 Thus, agreement between ProTime and laboratory INRs appears comparable with or better than that reported with other machines.…”
Section: Discussionsupporting
confidence: 68%
“…14 25 Another study found only 40% of paired samples within 0.5 INR units of each other. 26 Thus, agreement between ProTime and laboratory INRs appears comparable with or better than that reported with other machines.…”
Section: Discussionsupporting
confidence: 68%
“…This r valuewas actually superiorto r values reported in other portable monitor studies. 33,34,[37][38][39] Forall samples, 71.3% ofthe monitor INR measurements were within 0.1 INR unit ofthe laboratory reference; 83.2% were within 0.2INR unitofthelaboratory reference; 86.1qtij were within 0.3INR unit ofthe laboratory reference; 90.1 % were within 0.5INR unit of the laboratory reference; and 970/0 were within 1.0INR unit ofthe laboratory reference (Table I). These values were consistent with and in some casessuperior tovalues reported in otherstudies.…”
Section: Discussionmentioning
confidence: 99%
“…Laboratory control of oral anticoagulant treatment without adequate reference to sensitivity of the laboratory technique and reagent may have an adverse effect on clinical management, 6 '" and the INR system has undoubtedly contributed to improvement in this respect.4 Use of conventional thromboplastins for determination of INR within laboratories has been supplemented by the availability of portable near-patient testing instruments.58 10 In the present study we evaluated one such analyser in respect of INR determinations of both citrated plasma and citrated venous whole blood and compared results to those obtained with conventional reagents and techniques.…”
Section: Discussionmentioning
confidence: 99%